Analisis Faktor Yang Mempengaruhi Indeks Pembangunan Manusia Di Indonesia Tahun 1990-2014 - Hapsari, Anindita Budhi; , Dr. Daryono Soebagiyo, M.Ec (2016)
This study entitled "Analysis of Factors Affecting Human Development Index in Indonesia in 1990-2014". The purpose of this study was to analyze the dependent variable is the independent variable is IPM then government budgets in education, poverty, and GDP if all three have a significant effect. Data obtained form of time series sourced from the Central Statistics Agency (BPS) in Indonesian statistics from the year 1990 to 2014. The method used in this research is Multiple Linear Regression (OLS). Data obtained form of time series sourced from the Central Statistics Agency (BPS) in Indonesian statistics from the year 1990 to 2014. The method used in this research is Multiple Linear Regression (OLS). This study has a confidence level of 96.8%, which is expressed by R-Squared value of 0.968140. And the remaining 3.2% can be affected by other factors that are not included in the model.